FAKTOR RISIKO KEJADIAN GIZI KURANG PADA BALITA (Studi Kasus di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang) - Billy Suyatman; Siti Fatimah Pradigdo; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Malnutrition have a direct impact to cognitive and development impediment in toddlers. Bandarharjo Health Center have the highest prevalence of malnutrition in 2015 in Semarang City which reached 10.82%. The aim of this research was to analyze the risk factors of malnutrition in toddlers in Bandarharjo Health Center Working Area, Semarang City. This was a quantitative research with case control design. Population of this research were toddlers with malnutrition and normal nutrition in Bandarharjo Health Center Working Area, Semarang City in total of 3865 toddlers. The subject of this research were 146 toddlers consisting of 73 case samples (malnutrition) and 73 control samples (normal nutrition) whom selected by proportional random sampling technique. The result of this research showed that the variables is the risk factors of malnutrition in toddlers are mother with basic education level (OR = 28.2 ; 95% CI : 6.4 -123.6), family members > 4 people (OR = 12.1 ; 95% CI : 7.3 – 103.9), bad eating habbits (OR = 20.2 ; 95% CI : 9.5 – 97.8), bad health behaviour (OR = 35 ; 95% CI : 11.4 – 107.3), lack of energy adequacy (OR = 25.2 ; 95% CI : 5.7 – 110.7), lack of protein adequacy (OR = 35.7 ; 95% CI : 6,9 – 220.9). Advice for Bandarharjo Health Center to give counseling for mother to train their child to wash their hands before eat, to give exclusive breastfeeding to their baby until age 6 months and also to give animal protein to their child.